Humic Acid and Biofertilizer Applications Enhanced Pod and Cocoa Bean Production during the Dry Season at Kaliwining Plantation, Jember, East Java, Indonesia - Rohman, Fadil; Wachjar, Ade; Santosa, Edi; Abdoellah, Soetanto (Department of Agronomy and Horticulture, IPB University, 2019)
Cocoa (Theobroma cacao L.) is an important crop in Indonesia, but many farmers still face problem in improving bean production. This research aimed to evaluate the effect of humic acid and biofertilizer applications on pod growth and yield of cocoa. The research was conducted at Kaliwining Plantation managed by Indonesian Coffee and Cocoa Research Institute at Jember District, East Java, Indonesia from June 2017 to February 2018. The experiment used mature tree of Sulawesi from one clone. Treatment used were humic acid at level of 0, 1000, 2000, 3000 and 4000 ppm in combination with biofertilizer at level of 0, 500, 1000, 1500 and 2000 ppm that were applied through soil and foliar respectively. Results of this experiment showed that there was an interaction between humic acid and biofertilizer on beans number per plant and photosynthesis rate. Plants treated with 1000 ppm humic acid produced the highest number of small cherelle. Biofertilizer applied at 1500 ppm increased cherelle number, healthy cherelle, number of young pods, number of harvested pods, bean weight per plant and bean yield. The combination of 1000 ppm humic acid and 1500 ppm biofertilizer increased bean production by 39.7%. The high bean production was in line with the high photosynthetic rate. Thus, humic acid and biofertilizer applications could be a way to increase cocoa bean production in this area.